132 THE FEMALE PHENOTYPE OF OTO-PALATO-DIGITAL SYNDROME TYPE 2— A REVIEW AND REPORT OF POSSIBLE NEW FEATURES. (1st January 2005) - Conway, R.; Graham, J.; Falk, R.
Abstract : Oto-Palato-Digital (OPD) syndrome has recently been determined to be caused by mutations in Filamin A, encoded by the FLNA gene on Xq28. Filamin A is a structural protein which is expressed in diverse tissues and functions in cytoskeleton organization. Mutations in different functional domains of the protein result in similar but distinct disorders, including OPD types 1 and 2, Melnick-Needles syndrome, and frontometaphyseal dysplasia. OPD-1 was first characterized by Taybi in 1962 and over 30 cases have since been described in the literature. Principal features include broad forehead, hypertelorism, cleft palate, short stature, conductive hearing loss, and various anomalies of the hands and feet including broad (spatulate) toes, clinodactyly, syndactyly, and mild to moderate mental retardation. Female heterozygotes typically exhibit a milder phenotype with regard to all salient features, with normal intelligence, subtle facial dysmorphism, and mild involvement of the fingers or toes. OPD-2, first delineated by Fitch in 1976, presents a dramatically more severe phenotype in all respects, with frequent early lethality in affected males and a phenotype in female carriers that closely approximates males with OPD-1. Patients with OPD have been described whose phenotypes fall between the two disorders, suggesting a spectrum of severity rather than distinct clinical entities. We report a 22 year old female with dysmorphic features resembling OPD-2, including short stature, wide forehead, hypertelorism, antimongoloid slant to palpebral fissures, low-set, posteriorly rotated ears, small mandible, submucosal cleft palate with bifid uvula, clinodactyly and camptodactyly, broad distal digits, and flexion contractures. Radiographs reveal Klippel-Feil anomaly and spondylolysis of L5-S1, uncommon but reported findings in this condition. This patient also exhibits marked keloid formation at surgical scars, focal myocardial hypertrophy which necessitated surgical resection, and a bicornuate uterus. Neither the tissue overgrowth, nor the uterine malformation has been described previously in reported cases of females with OPD. A review of the literature will be presented with comparison of the findings in this patient to those in other reported females. Data on mutational analysis in females with this disorder is limited to date. Molecular analysis is planned and will be reported if available.